TECTONIC EVOLUTION OF FOREARC SIBOLGA BASIN, NORTH SUMATRA - Endartyanto, Aris
Tectonic setting and structures in the NW Sumatra affected by the oblique subduction of the Indo-Australian plate with the Sunda Microcontinent, forming a complex tectonic zone. The basin was included in the classification of frontier basin (sedimentary basins with hydrocarbon indications). Recently, the basin was a trending topic in the world of exploration due to the allegations stating that Sibolga Basin has huge gas reserves found in Miocene carbonate. Sibolga Basin is geographically located off the NW coast of Sumatra and in the western part is bordered by the Simulue Island and Mentawai Fault System. The basin extends along the NW-SE axis approximately 260 km and 100 km in SWNE direction. The basin has a maximum depth of 1300 m and has a thickness of Neogene sediments are deposited more than 6 seconds two way time, which represents the bulk composition of clastic sediments are thought derived from the Sumatra Island. There are four main periods of tectonic in Sibolga Basin, include the Pre-rift Unit (Middle Eocene), Syn-rift Unit (Late Eocene – Late Oligocene?), Post-rift Unit (Middle Miocene – Late Miocene), Syn-kinematic Unit (Pliocene – Recent). Sibolga basin formation began in the Late Eocene marked by Sequence I deposition. Rifting of graben complex evolved into relatively NNE – SSW direction before experiencing rotation into NE – SW trending in the Neogene. The pattern of main structure in the Sibolga Basin is Strike Slip Fault that has NW – SE direction which is formed in the Pliocene – Pleistocene, and normal fault that has NE – SW direction associated with rifting phase duuring the Late Eocene. The structure exist in the study area represents a different structural pattern, structure NE – SW normal fault formed by the extension deformation during subduction has a parallel trending to the Sumatra island (Late Eocene), whereas dextral strike slip fault with NW – SE ternding formed by compressional deformation due to oblique subduction.